2010
DOI: 10.1128/jb.00116-10
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequence of the Edible Cyanobacterium Arthrospira sp. PCC 8005

Abstract: We determined the genome sequence of Arthrospira sp. PCC 8005, a cyanobacterial strain of great interest to the European Space Agency for its nutritive value and oxygenic properties in the Micro-Ecological Life Support System Alternative (MELiSSA) biological life support system for long-term manned missions into space.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 6 publications
0
44
0
Order By: Relevance
“…As stated earlier, the sequences of the gvpA1, gvpC1, gvpA2 and gvpC2 genes cannot be found in the genome sequencing data of Arthrospira sp. PCC 8005 (Janssen et al, 2010), A. maxima CS-328 and A. platensis NIES-39 (Fujisawa et al, 2010) in public databases. The results presented in this paper should prove helpful for the final assembly of these and other Arthrospira genomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As stated earlier, the sequences of the gvpA1, gvpC1, gvpA2 and gvpC2 genes cannot be found in the genome sequencing data of Arthrospira sp. PCC 8005 (Janssen et al, 2010), A. maxima CS-328 and A. platensis NIES-39 (Fujisawa et al, 2010) in public databases. The results presented in this paper should prove helpful for the final assembly of these and other Arthrospira genomes.…”
Section: Discussionmentioning
confidence: 99%
“…PCC 8005 was performed in parallel to this study (Janssen et al, 2010). Our sequences resulting from the PCR products and containing the gvpA-gvpC fragments were first used to search for the corresponding sequences in the contigs or fragments of the genome of Arthrospira sp.…”
Section: Sequencing and Sequence Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…PCC 8005 revealed that these strains also contain multiple genes encoding putative restriction endonucleases. [7][8][9] Therefore, in order to apply bioengineering techniques to this species, it is important to characterize its restriction and modification (R/M) systems. The resulting knowledge will help provide means for evading the degradation of DNA molecules introduced into cells during gene-transfer experiments; specifically, it will allow design of DNA molecules devoid of susceptible sequences, as well as modification of DNA by cognate methylation enzymes to prevent recognition and cleavage at restriction sites.…”
mentioning
confidence: 99%
“…PCC 8005 indicate that the genomes of these strains contain many more putative restriction enzyme genes than expected from previous biochemical studies. [7][8][9] As shown in Table 1, the genome of A. platensis NIES-39 contains genes encoding putative proteins having significant homology to BsiWI, SnaBI, HgiCI, and HgiDI, which correspond to four of the nine isoschizomers that had been detected in Arthrospira strains by biochemical studies. In the case of A. plantensis C1 and Arthrospira sp.…”
mentioning
confidence: 99%